EVALUASI SUSUT DAYA PADA JARINGAN DISTRIBUSI PENYULANG GRAHA KOTA DI KABUPATEN SIDOARJO DENGAN METODE MODIFIED CARSON - Rifki, Mohammad Ya’kub Rizal; Hasanah, Rini Nur; Wijono, n/a (Jurnal Mahasiswa TEUB, 2024)
Electrical power loss is a crucial issue for PLN. To avoid a total blackout on the system, rotating blackouts are often carried out. This causes the electrical power supplied to consumers to be smaller than it should be. This power loss always exists because the equipment used does not have a 100% efficiency level. There are developments in the electricity distribution network which is becoming more complex with an increase in consumers, the addition of new branches, and variations in load additions. More systematic methods are needed to calculate and manage these losses. In this research, the Modified Carson calculation process and simulation were carried out using the ETAP 19.0.1 application which aims to determine the power loss in the Graha Kota feeder. In this feeder there are 2 types of phase cables, namely 150 mm2 and 240 mm2 phase cables, and a load of 15391.26 kVA, then this data is entered into the Modified Carson calculation to get the Modified Carson impedance value. Then a simulation is carried out on the ETAP 19.0.1 application to get the results of existing losses and Modified Carson power losses. From the results of the analysis carried out, the percentage of total power loss to the existing system power is 7.49%. Meanwhile, the percentage of total power loss on the power of the Modified Carson system produces a total power loss percentage of 10.69%. The percentage difference between the two methods is 3.2%. Referring to SPLN 1:1987, the permitted power loss is only 10%, so the calculation results of the Modified Carson method which involves more accurate impedance do not meet the established standards, so efforts are needed to reduce losses on the Graha Kota feeder. Keywords: Power Loss, Feeder, Distribution